Using illustrated system analysis for qualitative risk assessment of emptying of pit latrines - Tsai, Jocelyn; Wilson, Noel; de los Reyes, Francis L. (Frontiers in Environmental Science, 2022)
Pit latrines as the primary means of sanitation for billions of people. Fecal sludge must be removed regularly when pit latrines fill up, and the workers who empty these latrines are essential service providers. Pit latrine emptying services and approaches are highly variable, ranging from highly trained teams using vacuum trucks with a suite of personal protective equipment to individuals with no protection using simple manual tools like buckets and shovels. While national governments and nonprofits endeavor to make pit latrine emptying safer, the people making day-to-day decisions such as local pit emptying associations, sanitation businesses, utilities, and local governments have limited resources to evaluate how different emptying practices vary in terms of risk. In this paper we describe the development of an open-source Illustrated Systems Analysis tool for the fecal sludge management community. This tool can be used in conjunction with a simple risk assessment matrix to help decision makers describe, compare, and prioritize risks for mitigation. We demonstrate this process by outlining how a pit emptying team can compare mechanical and manual emptying with respect to ingestion of fecal material and inhalation of fecal bioaerosols. Illustrated Systems Analysis can be a tool to analyze fecal sludge management systems, and the associated challenges and opportunities so that they could be understood and referenced by the wider public and used to spark innovation. We provide a library of graphics freely under creative commons.